Politik Pergerakan Soekarno Saat Pengasingannya di Bengkulu Tahun 1938-1942 - Novita Dwi Anggraeni; Ira Miyarni Sustianingsih; Sarkowi (Criksetra: Jurnal Pendidikan Sejarah, 2021)
This study aims to describe the politics of Soekarno movement during his exile in Bengkulu in 1938-1948. The research method used in this research is historical research there are heuristic, source criticsm, interpretation and historiography. The results showed that the political movement of Soekarno during his exile in Bengkulu in 1938-1942, among others, Soekarno succeeded in instilling influence and spreading the idea of nationalism in various activities. In the Muhammadiyah organization, Soekarno succeeded in holding a conference throughout the Sumatran Muhammadiyah which was named the Daeratul Kubra Conference which had the aim in addition to improving the quality of education and teaching Soekarno also conveyed messages of nationalism, led and made theater texts which had the meaning of the conditions for struggle and nationalism understanding smart debate club as a forum for critical thinking of the people of Bengkulu, besides that Soekarno was also the pioneer and unifier of the Bengkulu people in the process of renovating the Jamik Bengkulu Mosque.